1999
DOI: 10.1016/s0895-7061(98)00235-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of myocardial infarct size by inhibition of inducible nitric oxide synthase

Abstract: The inducible nitric oxide synthase isoform (iNOS) is upregulated by cytokines and endotoxins in many types of cells, including cardiac myocytes. Nitric oxide (NO) induced by cytokines can be cytotoxic, and has been implicated in the pathophysiology of myocardial infarction, cardiomyopathy, and septic shock. To examine the role of iNOS in the ischemic myocardium, we studied: 1) the time course of expression of iNOS mRNA after myocardial infarction (MI) in male Sprague-Dawley rat hearts and expression of iNOS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 31 publications
4
44
3
Order By: Relevance
“…However, the pathophysiological significance of iNOS induction in HF is not clear. We and others have shown that pharmacological inhibition of iNOS significantly reduced infarct size in rats with acute myocardial ischemia (38) and prevented cardiac dysfunction and heart failure post-MI (31). In the present study, we found that mice lacking iNOS had better preserved cardiac function and tended to have less severe chamber dilatation and myocyte hypertrophy post-MI.…”
Section: Effect Of Inos Deficiency On Cardiac Remodeling and Dysfunctsupporting
confidence: 68%
See 1 more Smart Citation
“…However, the pathophysiological significance of iNOS induction in HF is not clear. We and others have shown that pharmacological inhibition of iNOS significantly reduced infarct size in rats with acute myocardial ischemia (38) and prevented cardiac dysfunction and heart failure post-MI (31). In the present study, we found that mice lacking iNOS had better preserved cardiac function and tended to have less severe chamber dilatation and myocyte hypertrophy post-MI.…”
Section: Effect Of Inos Deficiency On Cardiac Remodeling and Dysfunctsupporting
confidence: 68%
“…We and others have reported that selective inhibition of iNOS reduced infarct size in rats with acute coronary artery occlusion (38) and ameliorated cardiac dysfunction in strokeprone spontaneously hypertensive rats (1). Deletion of the iNOS gene attenuated endotoxin-induced myocardial dysfunction (36), VCAM-1 expression, and neointima formation in mice with arterial injury (6), while overexpression of iNOS in the heart resulted in a generation of OONO Ϫ , heart block, and sudden death (29).…”
mentioning
confidence: 95%
“…21 In the rat, NOS2 mRNA expression in the infarcted region peaked 6 hours after coronary ligation and returned to baseline by 1 week. 22 Likewise, in the mouse, we found that NOS2 mRNA was increased in the infarct region at 3 days after MI, peaked at 7 days, and returned to baseline by 14 days. 23 NOS2-derived NO can cause myocyte apoptosis.…”
Section: Lack Of Effect On MI Sizesupporting
confidence: 57%
“…Furthermore, in the setting of brief ischemia followed by reperfusion, we are interested in whether the reduction in TTC-negative tissue observed in early reperfusion signifies genuine reduction of eventual infarct size following extended reperfusion. Because the stained myocardium consists of a complex mixture of necrotic and surviving myocytes in the early reperfusion, at that time the method of TTC staining has limitations in its accuracy for evaluation of cell necrosis (24); furthermore, inducible NO synthase (iNOS) induced by proinflammatory cytokines occurring during the late phase of postischemic infarction could increase infarct size (47)(48)(49).…”
mentioning
confidence: 99%